Biofuels : Lines of debate around the production of agrofuels worldwide - Gómez Rodríguez, Dustin Tahisin (2021)
The overall objective of the article is to characterize trends in biofuel production worldwide. The methodology is qualitative, and the method is of documentary review by matrices with an observation window of the last decade. The main results in reference to the lines of discussion around the production of agrofuel worldwide are from the legislation underpinning the legal environment of trade; secondly, prices; third trade; fourthly production and finally the impact of production on the environment. The main conclusion is that there is scientific evidence that establishes the advantages and disadvantages of biofuel production both economically, socially, politically, and environmentally. One way the agribusiness of biofuels has responded to is through the use of technologies to minimize the effects of production. An example of this is second-generation biofuels. However, there is still a long way to go to say that they are the best choice from the economic, environmental, and social dimensions.